ANALISIS PEMANFAATAN APLIKASI CANVA PADA KEMAMPUAN LITERASI DIGITAL SISWA KELAS 3 SD SAMADIKUN KOTA CIREBON - Harina; Nailah Tresnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of the Canva application in learning in grade 3 at SDN Samadikun Kota Cirebon has proven to improve students' digital literacy. Although there were initial challenges in using devices such as Chromebooks, students began to access, evaluate, manage, and create digital content more effectively. Canva also encourages students' creativity in designing posters that align with the Indonesian language lesson materials. Additionally, collaborative activities within groups enhance communication and digital collaboration among students. This study uses a descriptive qualitative approach with triangulation techniques through observation, interviews, and documentation. The purpose of this study is to analyze how the Canva application supports the improvement of students' digital literacy in the context of poster-making lessons.